Choroidal thickness measurement in healthy pediatric population using Cirrus HD optical coherence tomography - Tenlik,Aylin (2015)
Purpose: To investigate the association between central choroidal thickness (CT), axial length (AL), age, gender, and refractive error in a healthy pediatric population using optical coherence tomography (OCT). Methods: This institutional study involved 137 healthy children (57 boys, 80 girls) aged between 4 and 18 years. Each child underwent a dilated eye examination, cycloplegic refraction, and AL measurement using a Nidek AL-Scan optical biometer. The central foveal thickness (CFT) and CT were measured using Cirrus high definition (HD)-OCT. The right eye of each subject was selected for analysis. Results: The mean age of the children was 10.0 ± 4.7 years (range, 4-18 years). The mean spherical equivalent (SE) was -0.24 ± 1.24 diopters (D) (range, -2.00 D to +2.25 D). The mean AL was 23.1 ± 1.2 mm (range, 20-27 mm). The mean central CT was 388.2 ± 50.0 μm and was not correlated with age, gender, AL, or refractive error. Conclusion: The data provide a pediatric normative database of CT using enhanced depth imaging OCT. This information may be useful in the diagnosis and monitoring of retino-choroidal diseases in children.